RELATIONSHIP OF CARING CARE BEHAVIOR WITH PATIENT SATISFACTION IN THE CARE ROOM PUSKESMAS PAJANG KOTA SURAKARTA - Diah Ardian Rukmana; Rif Atiningtyas Haris; Ari Setiyajati (Jurnal Ilmu Keperawatan Indonesia (JIKI), 2020)
Background: Puskesmas is a health service place that is directly related to the community. The Puskesmas is a Community Health Center located in the sub-districts which was initiated in the 1960s (Hartono 2010). Patient dissatisfaction arises because of the gap between the expectations of patients and the performance of health services theyfeel when using health services (Pohan, 2009). Caring is central to nursing, explaining concern as based on a universal set of human values (kindness, caring, and love for selfand others).Research Objective: To Analyze the Relationship between Nurse Caring Behavior and Patient Satisfaction in the Nursing Room of Pajang Surakarta Health CenterResearch Method: This type of research is descriptive correlational with a crosssectional approach. The population is all patients undergoing treatment in the Nursing Room of Pajang Surakarta Public Health Center, amounting to 62 people. Samples of 39 respondents with purposive sampling technique. Data Analysis using Rank-Spearman.The Results of the study: The results of the study revealed that according to the respondents the most nurses behaved in sufficient caring categories. According to Potterand Perry (2014) Caring is giving full attention to clients when providing nursing care. Nursalam (2014) nurse caring behavior is a caring attitude that makes it easier forpatients to achieve health and recovery improvement.Conclusion: There is a relationship between Nurses' Caring Behavior and Patient Satisfaction in the Nursing Room of Pajang City Public Health Center